Astragalus polysaccharides meliorate cardiovascular dysfunction in iron-overloaded thalassemic mice. Issue 14 (October 2019) - Yang, Xue; Zhu, Xiaoxi; Tang, Xianying; Liu, Mei; Zheng, Huiling; Zheng, Lin
Astragalus polysaccharides (APS) are well-known oriental herbal medicine ingredients with various bioactivities. Herein we aimed to explore the regulation of APS in the iron overloaded β-thalassemic mice. Iron diet was provided to induce iron-overload condition in wild-type and β-thalassemic mice, to which APS was administered by gavage. The heart weight index, hemoglobin, left ventricular function, heart rate variability (HRV), cardiac iron and malondialdehyde, reactive oxygen species (ROS) and cardiac apoptotic proteins including Bax, Bcl-2, and caspase3 were detected among different mouse groups. Iron overload led to the impaired left ventricular function and HRV, plasma non-transferrin-bound iron, ROS, and cardiac mitochondrial function in thalassemic mice. Our data suggested that in thalassemic mice with iron-overload, APS administration showed benefits in alleviating iron accumulation and oxidative stress, ameliorating HRV and left ventricular function, without altering the cardiac apoptosis proteins. Our results demonstrated that APS effectively attenuated cardiovascular dysfunction via regulating oxidative stress, while the levels of cardiac apoptotic proteins remained unchanged. Impact statement: Currently iron chelation therapy is the standard treatment to inverse the iron-overload in thalassemia patients. However, inevitable side effects along with passable cardio-protective efficacy have been reported. In this study, astragalus polysaccharides (APS) treatment effectively attenuated cardiovascular dysfunction via regulating oxidative stress in β-thalassemic mice, while the levels of cardiac apoptotic proteins remained unchanged. Our study highlights the therapeutic potentials of APS in the treatment of iron-overloaded disorders.